2018
DOI: 10.3889/oamjms.2018.271
|View full text |Cite
|
Sign up to set email alerts
|

A Saudi Infant with Vici Syndrome: Case Report and Literature Review

Abstract: INTRODUCTION:Vici syndrome, a rare autosomal recessive disorder, was first described in 1988 by Vici et al. Only 78 cases have been reported to date. The syndrome is characterised by agenesis of the corpus callosum, hypopigmentation, cardiomyopathy, progressive failure to thrive, dysmorphic features, immunodeficiency and cataracts. Mutations in the gene epg5 have been identified as the cause of Vici syndrome.CASE DESCRIPTION:The parents are a consanguineous Saudi couple with two other children diagnosed with G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(32 reference statements)
0
9
0
Order By: Relevance
“…Intractable diarrhea developed in the female patient and was suggested to be secondary to malabsorption. This consequence is supposed to be linked to EPG5 ‐related autophagy depletion (Alzahrani et al., ; Hedberg‐Oldfors et al., ; Huenerberg et al., ; Shimada et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intractable diarrhea developed in the female patient and was suggested to be secondary to malabsorption. This consequence is supposed to be linked to EPG5 ‐related autophagy depletion (Alzahrani et al., ; Hedberg‐Oldfors et al., ; Huenerberg et al., ; Shimada et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these phenotypic features, cardiomyopathy, developmental delay, microcephaly, and failure to thrive were described as typical consequences (Byrne et al., ; Chiyonobu et al., ; del Campo et al., ). Since the first description, more than 40 families have been published with Vici syndrome (VICIS), who were compatible with an autosomal recessive transmission and have extended the variable clinical spectrum with myopathy, epilepsy, elevated aminotransferases, thymus aplasia, thrombocytopenic purpura, sensorineural hearing loss, and renal tubular acidosis (Aggarwal, Tandon, Bhowmik, & Dalal, ; Al‐Owain et al., ; Alzahrani, Alghamdi, & Waggass, ; Balasubramaniam et al., ; Byrne et al., ; Chiyonobu et al., ; Cullup et al., ; del Campo et al., ; Demiral, Sen, Esener, Ceylaner, & Tekedereli, ; El‐Kersh, Jungbluth, Gringras, & Senthilvel, ; Hedberg‐Oldfors, Darin, & Oldfors, ; Hori et al., ; Huenerberg et al., ; Maillard et al., ; McClelland et al., ; Miyata et al., ; Ozkale, Erol, Gümüs, Ozkale, & Alehan, ; Rogers, Aufmuth, & Monesson, ; Said, Soler, & Sewry, ; Shimada et al., ; Waldrop et al., ). The prognosis was found to be poor with a median survival of 42 months (Byrne, Dionisi‐Vici, Smith, Gautel, & Jungbluth, ).…”
Section: Introductionmentioning
confidence: 99%
“…Miyata et al (2007) also recorded two sibling patients suffering from VICIS, but the elder sister died at the age of 12 months because of heart failure. In 2018, Alzahrani and his colleges described a Saudi male infant affected by VICIS and died at the age of 8 months (Alzahrani et al, 2018). In the same year, Demiral et al reported a Turkish male patient died of VICIS due to sepsis at 1 year and 9 months old (Demiral et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The condition was first described by the Italian physician Carlo Dionisi-Vici and colleagues in 1988, in two Italian brothers who died at 2 and 3 years of age due to bronchopneumonia. Since then, less than a hundred cases have been described worldwide, with a global prevalence of less than 1/1,000,000 ( Alzahrani et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%